Relationships between self-determination theory and theory of planned behavior applied to physical activity and exercise behavior in chronic pain. Issue 7 (9th August 2017) - Brooks, Jessica M.; Iwanaga, Kanako; Chiu, Chung-Yi; Cotton, Brandi Parker; Deiches, Jon; Morrison, Blaise; Moser, Erin; Chan, Fong
Abstract: This study examined the relationships between self-determination theory (SDT) and theory of planned behavior (TpB) applied to physical activity and exercise behavior (PA&E) in people with chronic pain. Two hundred and eleven adults with chronic musculoskeletal pain (28 males and 183 females, age range 18 to 82 years, mean age 43 years) were recruited from online support groups and clinic networks in the United States. Participants completed SDT measures relevant to PA&E on perceived autonomy support, autonomy, competence, and relatedness, as well as TpB measures relevant to PA&E on intention, attitudes, subjective norms, and perceived behavioral control. Correlational techniques and canonical correlation analysis were performed to examine the relationships and variance within and between theoretical dimensions. Overall, the SDT set accounted for 37% of the TpB variance and the TpB set accounted for 32% of the SDT set variance. The results indicate there are statistical similarities and differences between concepts in SDT and TpB models for PA&E. Using both empirical guidance and clinical expertise, researchers and practitioners should attempt to select and integrate non-redundant and complementary components from SDT, TpB, and other related health behavior theories.